Corporate Venture Capital and the Nature of Innovation - Hannes Maxin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The present paper solely focuses on the investment decisions of two corporate venture capital firms. These investors have to decide whether to finance a wealthless venture alone or to share the profits and the costs with the other investor, called syndication. The critical point are the innovation objectives of the corporate investors respectively the nature of innovation of the venture. To my knowledge, no other theoretical paper considers such a financing situation consisting of two CVCs.
Keywords: G24; M13; 330